Extending access to low-cost private schools through vouchers: an alternative interpretation of a two-stage 'School Choice' experiment in India. (2nd September 2016) - Tooley, James
Abstract: Muralidharan and Sundararaman report a randomised controlled trial of a school voucher experiment in Andhra Pradesh, India. The headline findings are that there are no significant academic differences between voucher winners and losers in Telugu, mathematics, English, and science/social studies, although because the private schools appear to use time more efficiently, they are also able to teach Hindi (the national language). The average per capita cost in private schools is less than a third of that in public schools. So while private schools are more efficient, they are not necessarily leading to higher standards. There are two types of private school in the experiment, English and Telugu medium. Since tests in non-language subjects were conducted in a different language for children in public and English-medium private schools, the results in mathematics and science/social studies are difficult to interpret. There are suggestive comparisons between children in Telugu-medium private and public schools, where children took tests in the same language (and were also not subject to disruption in medium of instruction), which show that students in private schools outperform those in public in all subjects. This suggests that giving children access to private schools through vouchers could be a very important policy reform.